2018
DOI: 10.2147/cmar.s151945
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution and age-related outcomes of olfactory neuroblastoma: a population-based analysis

Abstract: ObjectiveThe objective of the study was to describe the age distribution and to evaluate the role of prognostic value of age on survival in patients diagnosed with olfactory neuroblastoma (ONB). A population-based retrospective analysis was conducted.Materials and methodsThe population-based study of patients in the Surveillance, Epidemiology, and End Results (SEER) tumor registry, who were diagnosed with ONB from 1973 to 2014, were retrospectively analyzed.ResultsThe cohort included 876 patients with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…The only Kadish A tumor in our series was related to an early incidental diagnosis (brain computed tomography [brain‐CT] scan performed for cranial trauma). In adults, this staging system remains a significant predictor of survival . Our results confirmed this observation showing that patients with high‐stage tumors (Kadish C‐D) have a significantly worse prognosis than patients with low‐stage tumors (Kadish A‐B), 5‐year OS 100.0% versus 28.6 ± 12.1% (log‐rank P = .032).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The only Kadish A tumor in our series was related to an early incidental diagnosis (brain computed tomography [brain‐CT] scan performed for cranial trauma). In adults, this staging system remains a significant predictor of survival . Our results confirmed this observation showing that patients with high‐stage tumors (Kadish C‐D) have a significantly worse prognosis than patients with low‐stage tumors (Kadish A‐B), 5‐year OS 100.0% versus 28.6 ± 12.1% (log‐rank P = .032).…”
Section: Discussionsupporting
confidence: 83%
“…However, the relevance of a modified Kadish classification is still under debate . Indeed, Kadish C tumors constitute a very heterogeneous group related by their extension beyond paranasal sinuses, but without discrimination regarding involved anatomic sites . In our study, we observed 10 local recurrences in the initial Kadish C tumor with involvement of the anterior cerebral fossa and, among them, six with meningeal progressions.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…With the increasing of age, somatic mutations are accumulating, contributing to the high incidence of cancer in older adults [1][2][3][4]. Moreover, old tumor patients demonstrate different histological characteristics and prognostic outcomes as compared with young tumor patients [5][6][7][8][9][10][11][12]. Those observations highlight the prognostic importance of age of tumor patients at initial pathologic diagnosis.…”
Section: Introductionmentioning
confidence: 98%